Organochlorine pesticide residues in sediments from the Uganda side of Lake Victoria - Wasswa, John; Kiremire, Bernard T.; Nkedi-Kizza, Peter; Mbabazi, Jolocam; Ssebugere, Patrick (Chemosphere, 2011)
Organochlorine (OC) residues were analysed in 117 sediment samples collected from four bays of the Uganda side of Lake Victoria. The sediments were collected with a corer at a depth of 0–20 cm, and extracted for OC residues using a solid dispersion method. The extracts were cleaned using gel permeation chromatography and analysed for pesticide residues using a gas chromatograph (GC) equipped with an electron capture detector. The results were confirmed using a GC equipped with a mass spectrometer (MS). A total of 16 OC residues, most of them persistent organic pollutants (POPs) were identified and quantified. The OC residue levels were expressed on an oven dry weight (d.w.) basis. Endosulphan sulphate, in the range of 0.82–5.62 lg kg 1 d.w., was the most frequently detected residue. Aldrin and dieldrin were in the ranges of 0.22–15.96 and 0.94–7.18 lg kg 1 d.w., respectively. DDT and its metabolites lay between 0.11–3.59 for p,p0-DDE, 0.38–4.02 for p,p0-DDD, 0.04–1.46 for p,p0-DDT, 0.07–2.72 for o,p0-DDE and 0.01–1.63 lg kg 1 d.w. for o,p0-DDT. The levels of c-HCH varied from 0.05 to 5.48 lg kg 1 d.w. Heptachlor was detected only once at a level of 0.81 lg kg 1 d.w., while its photo-oxidation product, heptachlor epoxide, ranged between non-detectable (ND) to 3.19 lg kg 1 d.w. Chlordane ranged from ND to 0.76 lg kg 1 d.w. Based on the threshold effect concentration (TEC) for fresh water ecosystems, aldrin and dieldrin were the only OCs that seemed to be a threat to the lake environment.
Keywords: Persistent organic pollutants; Pesticides; Metabolites; Lake Victoria; Sediment